The Role of IL-33 in Experimental Heart Transplantation - Chen, Jie (Cardiol Res Pract, 2020)
Interleukin-33 (IL-33) is a member of the IL-1 family of proteins that are produced by a variety of cell types in multiple tissues. Under conditions of cell injury or death, IL-33 is passively released from the nucleus and acts as an “alarmin” upon binding to its specific receptor ST2, which leads to proinflammatory or anti-inflammatory effects depending on the pathological environment. To date, numerous studies have investigated the roles of IL-33 in human and murine models of diseases of the nervous system, digestive system, pulmonary system, as well as other organs and systems, including solid organ transplantation. With graft rejection and ischemia-reperfusion injury being the most common causes of grafted organ failure or dysfunction, researchers have begun to investigate the role of IL-33 in the immune-related mechanisms of graft tolerance and rejection using heart transplantation models. In the present review, we summarize the identified roles of IL-33 as well as the corresponding mechanisms by which IL-33 acts within the progression of graft rejection after heart transplantation in animal models.